Performance of M&A Deals in The Russian Market: Evidence from Oil & Gas and Power Industries - LashukTatsiana; VasilevskiyMark; FilatovaEvgeniia (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2023)
The paper provides a comprehensive investigation of M&A deals on the Russian market, particularly in the Oil and Gas and Power sectors. This research fills the gap in literature by scrutinizing key M&A trends, reviewing M&A activities, and evaluating M&A performance through a combined application of Data Envelopment Analysis (DEA) and case study analysis. A critical part of this study involves exploring the influence of geopolitical factors on these transactions. The article presents a novel academic contribution by offering focused insights on M&A activities in two under-researched yet critical sectors of the Russian economy. Furthermore, the innovative use of DEA and case study analysis enhances our understanding of industry trends over a span of 22 years, including the M&A transactions of 2022. Our sample includes 23 deals made by 17 Russian companies in the Energy and Power industries. We selected deals as a result of which the acquirer companies obtained more than 50% of the target company, so the acquirer company gained control over the operations and performance of the acquired company. The study traces the effects of geopolitical influences on M&A outcomes, a critical consideration given Russia’s unique geopolitical context. This research is of practical significance for domestic and international businesses contemplating M&A decisions within Russia’s Oil & Gas and Power industries, offering valuable insights to guide future strategies. While this study uncovers promising positive trends, further exploration and long-term data are necessary for a complete assessment of the impact of these M&A activities on company performance.